2018
DOI: 10.3390/toxins10050089
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Mycotoxin Contamination of Food Commodities in Zimbabwe

Abstract: Agricultural products, especially cereal grains, serve as staple foods in sub-Saharan Africa. However, climatic conditions in this region can lead to contamination of these commodities by moulds, with subsequent production of mycotoxins posing health risks to both humans and animals. There is limited documentation on the occurrence of mycotoxins in sub-Saharan African countries, leading to the exposure of their populations to a wide variety of mycotoxins through consumption of contaminated foods. This review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 62 publications
(101 reference statements)
0
23
0
1
Order By: Relevance
“…Mycotoxins are secondary metabolites produced by fungal genera that are toxic, carcinogenic, and/or teratogenic, resulting in significant adverse effects food safety and public health [ 10 , 11 ]. Among the mycotoxins, zearalenone (ZEA, also known as F-2 toxin), a nonsteroidal estrogenic mycotoxin produced by various Fusarium species [ 12 ], is considered as a common contaminant of food and feedstuffs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxins are secondary metabolites produced by fungal genera that are toxic, carcinogenic, and/or teratogenic, resulting in significant adverse effects food safety and public health [ 10 , 11 ]. Among the mycotoxins, zearalenone (ZEA, also known as F-2 toxin), a nonsteroidal estrogenic mycotoxin produced by various Fusarium species [ 12 ], is considered as a common contaminant of food and feedstuffs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this stage bears center the related works of this investigations work. Mycotoxins are a heterogeneous gathering of little sub-atomic weight harmful contagious product with the capacity to reason issue in people and different vertebrates [1][2][3]. They are omnipresent and inescapable hazardous vendors [4] originate in practically a wide range of nourishments, alongside oats [5] and wheat subordinates [6], creature [7] and dairy [8] stock, organic products [9], and even wine [10,11].…”
Section: Related Workmentioning
confidence: 99%
“…Food safety is currently a priority in the processes of the production, processing and distribution of food products. Micro-fungi such as Penicillium, Fusarium and Aspergillus that grow on foods and feeds when conditions are suitable, are able to release secondary metabolites (mycotoxins) that endanger the health of humans and animals after being consumed [24][25][26][27][28][29][30][31]. The Centers for Disease Control and Prevention (CDC) reported that approximately 4.5 billion people are chronically exposed to mycotoxins [32].…”
Section: Introductionmentioning
confidence: 99%